THE EFFECT OF LIFETSYLE ON LUTEINIZING HORMONE LEVELS, TESTOSTERONE LEVELS AND INFERTILITY IN OBESITY MEN - Angga Bhaim Ibrahim (Jurnal Kesehatan Medika Saintika, 2022)
Obesity is a state of imbalance between incoming energy and outgoing energy over a long period of time (Hartono, 2008). Obesity is becoming an epidemic throughout the world, both in developed and developing countries, and two-thirds suffer from obesity (Stefan, 2010). The increase in obesity will reach 50% in 2025 for developed countries (Sudoyo, 2009). According to WHO (2013), there are 2.1 billion obese people in the world, Indonesia ranks 10th with a total of 40 million obese people, after the United States, China, India, Russia, Brazil, Mexico, Egypt, Germany and Pakistan. Was from Riskesdas (2013), adolescents aged 13-21 years in Indonesia suffer from 10.8% obesity, 8.3% obesity and 2.5% very obesity.                 In obesity, there is an increase in adiponectin and a decrease in resistin and RBP-4, resulting in the formation of fat cell adipocytes which affect the hormone testosterone (Ganong, 2012). Testosterone (17-hydroxyandrost-4-en-3) is the main androgen hormone synthesized in the testes and adrenal cortex. Testosterone is synthesized primarily in the leydig cells, whereas the leydig cells are regulated by luteinizing hormone (LH). The amount of testosterone synthesized is regulated by the hypothalamus-pituitary-testicular axis (Muller, 2013). When testosterone levels are low, gonadotropin-releasing hormone (GnRH) is released by the hypothalamus, which stimulates the anterior pituitary gland to release LH stimulating the testes to synthesize the hormone testosterone. Finally, it increases testosterone levels through negative feedback (Ganong, 2012). Some of the factors that cause a decrease in hormone levels are lifestyle such as smoking, stress and consuming alcohol.               The conclusion of the study is that there is an effect of lifestyle on LH levels, the hormone testosterone and infertility in obese men. Suggestions for future researchers to conduct research with a larger sample size.